A case series on the potential effect of omega-3-fatty acid supplementation on 24-h heart rate variability and its circadian variation in children with attention deficit (hyperactivity) disorder - Buchhorn, Reiner; Koenig, Julian; Jarczok, Marc N.; Kaess, Michael (ADHD Attention Deficit and Hyperactivity Disorders, 2018)
Attention deficit disorder with and without hyperactivity (ADHD) in children is associated with decreased 24-h heart rate variability (HRV). Previous research has shown that supplementation of omega-3-fatty acid increases HRV. Here, we aimed to investigate whether the supplementation of omega-3-fatty acids would increase 24-h HRV in an uncontrolled case series of children with ADHD. HRV was recorded in 18 children and adolescents (age 13.35 ± 2.8 years) before and after omega-3 supplementation. Preliminary results indicate that omega-3 supplementation in children with AD(H)D may reduce mean heart rate and increase its variability. Future studies would do well to implement randomized, placebo-controlled designs with greater methodological rigor.